Technical Teachers’ Self-Efficacy and Qualifications as Correlate on Students’ Academic Performance in Basic Technology - Jane Itohan Oviawe; David Omoh (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
Teacher qualification is one of the predictors of their self-efficacy which contributes positively to the students’ learning outcomes. Technical teachers' lack of confidence in Basic Technology classes has become a worsening element linked to their lack of certification and shallow knowledge, which has an unfavorable influence on students' learning outcomes. Using a correlational research methodology, this study assessed the technical instructors' self-efficacy and credentials as correlates of students' academic achievement in Basic Technology in Edo State. The population for the study was made up of 448 technical teachers. A multi-stage sampling method was adopted in the selection of schools for this study. Six local governments were selected as clusters and the schools were selected using a simple random sampling technique within the clusters. A purposive random sampling technique was used to sample 126 technical teachers involved in this study. The instruments used for data collection were Teacher Self-Efficacy Scale (TSES) with a Cronbach Alpha reliability of .76 and students' JSS III mock examination scores for their achievement. The data obtained were analyzed using Pearson Product Moment Correlation coefficient and regression analysis. The findings indicated that 40% of the difference in students' academic performance in Basic Technology was due to technical teachers' qualifications and that there was a strong link between technical teachers' self-efficacy and students' academic success in Basic Technology. The study's findings suggested, among other things, that technical teachers' self-efficacy should be taken into account when it comes to students' academic achievement in Basic Technology.